2019
DOI: 10.1111/ap.12399
|View full text |Cite
|
Sign up to set email alerts
|

“At night he cries from dreams”: Perceptions of children's psychological distress and wellbeing amongst parents with refugee or asylum seeker backgrounds in Australia

Abstract: Objective The objective of the current study was to gain insight into the ways in which parents who had arrived in Australia with refugee or asylum seeker backgrounds understand their young children's experiences of wellbeing and psychological distress during resettlement. Method Eight parents (three male and five female) who had arrived in Australia from Iran and Afghanistan with children aged between five and eight were recruited using purposive sampling. In‐depth interviews were conducted regarding their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Previous research has found that refugee children's wellbeing is negatively affected by the disruption of family structures (Due et al, 2019), and thus involvement with family should be considered carefully by practitioners. While the broader literature indicates that parent participation contributes to positive therapeutic outcomes for young people (Karver et al, 2006), this may not always be the case for this particular population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that refugee children's wellbeing is negatively affected by the disruption of family structures (Due et al, 2019), and thus involvement with family should be considered carefully by practitioners. While the broader literature indicates that parent participation contributes to positive therapeutic outcomes for young people (Karver et al, 2006), this may not always be the case for this particular population.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these methodological issues, and the overall lack of literature in the area, are likely caused by the barriers to research with refugees which include challenges with recruitment and follow up, the heterogeneity of refugee groups, ethical issues such as difficulties with having control groups, the need for interpreters, and limited culturally appropriate and validated assessment tools (Due et al, 2014;Ehntholt & Yule, 2006;Fazel & Betancourt, 2017). Nevertheless, given the critical importance of having an evidence base for competencies for refugee and asylum seeker children and young people, future research could usefully examine what are considered important competencies for practitioners working in this area, from both the practitioner perspective, as well as the perspective of the child or young person.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the setting of the care link in the plot scene is to allow more people to care to reduce the loneliness, boredom, and helplessness of the treated person. rough the completion of a task, a partnership has been established and their care and blessings are extremely important for the recovery of the disease [12]. Developmental obstacles generally include insufficient memory, defects in perception, unusual thinking skills and language flaws, and flaws in the ability to judge numbers.…”
Section: Matching Function Construction Of Children's Psychological Distress Scenementioning
confidence: 99%
“…These challenges have even led to poorer health condition among Afghan refugees compared with the general Australian population [ 16 , 17 , 18 ]. These issues are real, and this study documents the views of many people from Afghanistan who have gone through the long process, from being refugees to today being Australian citizens, who have been living in Perth for many years.…”
Section: Introductionmentioning
confidence: 99%